2021
DOI: 10.1182/blood-2021-150943
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of Venetoclax and Hypomethylating Agents (HMA) or Low-Dose Cytarabine (LDAC) for Patients with Acute Myeloid Leukemia (AML) - Real-World Data from Two German Academic Centers

Abstract: Introduction Treatment with the BCL-2 inhibitor Venetoclax (VEN) in combination with hypomethylating agents (HMA) or low-dose cytarabine (LDAC) has shown encouraging results in patients with acute myeloid leukemia (AML). In contrast to the FDA, EMA approval for unfit AML patients was given only recently, and VEN combinations have therefore often been used as off-label treatment for relapsed/refractory (r/r) AML patients. We conducted a retrospective study of 73 unfit or r/r AML patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Venetoclax is a selective BCL-2 inhibitor that is widely used to promote apoptosis in haematological malignancies [119]. The benefits of combining venetoclax and HMA treatment have been shown in several studies of AML, including treatment-naïve and r/r cases [120][121][122][123]. For example, one study reported superior responses in r/r patients (64% ORR vs. 19% AZA alone), as well as patients with IDH1/2 or TP53 mutations (67% ORR) [120].…”
Section: Combination Therapiesmentioning
confidence: 99%
“…Venetoclax is a selective BCL-2 inhibitor that is widely used to promote apoptosis in haematological malignancies [119]. The benefits of combining venetoclax and HMA treatment have been shown in several studies of AML, including treatment-naïve and r/r cases [120][121][122][123]. For example, one study reported superior responses in r/r patients (64% ORR vs. 19% AZA alone), as well as patients with IDH1/2 or TP53 mutations (67% ORR) [120].…”
Section: Combination Therapiesmentioning
confidence: 99%